A new class of hybrid anticancer agents inspired by the synergistic effects of curcumin and genistein: Design, synthesis, and anti-proliferative evaluation. Issue 20 (15th October 2015) - Chen, Qiao-Hong; Yu, Kevin; Zhang, Xiaojie; Chen, Guanglin; Hoover, Andrew; Leon, Francisco; Wang, Rubing; Subrahmanyam, Nithya; Addo Mekuria, Ermias; Harinantenaina Rakotondraibe, Liva
Graphical abstract